Gelatin-mycosporine-like amino acid-dialdehyde starch composite membrane as well as preparation method and application thereof

Through the preparation of gelatin-mycinoid amino acid-bialdehyde starch composite film, the problems of poor mechanical properties and insufficient anti-ultraviolet ability of existing UV packaging materials are solved, and efficient UV barriers and good biocompatibility are achieved.

CN119707738AActive Publication Date: 2025-03-28SHANDONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411893124.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing UV-resistant packaging materials have problems such as poor mechanical properties, non-renewability and insufficient degradability, and their UV-resistant ability is weak, making it difficult to apply to food or drug packaging that needs to be kept light-shielded and protected from light.

Method used

The gelatin-mycinoid amino acid-bialdehyde starch composite membrane is used to extract the mycinoid amino acids in the barbed nori and combine with gelatin and bialdehyde starch to form a composite membrane through cross-linking reaction to achieve the effect of anti-ultraviolet rays.

Benefits of technology

The prepared composite membrane has excellent mechanical properties, physical and chemical properties, anti-UV activity and good biocompatibility, which can effectively protect probiotics and extend the shelf life of strawberries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707738A_ABST
    Figure CN119707738A_ABST
Patent Text Reader

Abstract

The invention discloses a gelatin-mycosporine-like amino acid-dialdehyde starch composite membrane and a preparation method and application thereof.The preparation method of the composite membrane comprises the following steps that a cross-linking agent is added into a gelatin solution, after activation is conducted for set time, N-hydroxysuccinimide is added into the gelatin solution, then mycosporine-like amino acid is added into the gelatin solution, and the gelatin-mycosporine-like amino acid-dialdehyde starch composite membrane is obtained; under a weak acid condition, coupling in a dark place for a set time to obtain Gel-MAAs; the preparation method comprises the following steps: dissolving Gel-MAAs in water to obtain a compound solution; dialdehyde starch is dissolved in water, gelatinized and adjusted to be alkalescent, and a dialdehyde starch solution is obtained; dropwise adding a dialdehyde starch solution into the compound solution, uniformly mixing, reacting at 35-45 DEG C for 1-3 hours, adding 1-5% by mass of glycerol, performing ultrasonic degassing, pouring a membrane solution into a mold, and drying to obtain the membrane. The composite membrane has excellent mechanical properties, physical and chemical properties, anti-ultraviolet activity and good biocompatibility, and has great potential in the field of active composite membranes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-ultraviolet materials, and in particular relates to a gelatin-mycosporine-like amino acid-dialdehyde starch composite film and a preparation method and application thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Ultraviolet radiation exposes the environment to high-radiation of UV-B (280-315nm) and UV-A (315-400nm). Ultraviolet radiation can have a variety of harmful effects on biologically important molecules such as lipids, proteins or DNA. It can also change the performance and durability of non-living materials (such as rubber and textile materials). In addition, many medicines need to be stored in a dark place, mainly because ultraviolet radiation accelerates the oxidation of drugs. Some drugs can cause photochemical degradation, which not only reduces the potency of the drug, but also produces color and precipitation, seriously affecting the quality of the drug and even increasing the toxicity of the drug.

[0004] Anti-ultraviolet radiation packaging is generally made of dark glass or plastic. Glass has problems such as poor mechanical properties and poor impact resistance, and is not easy to store. Most plastic films are petroleum-based materials, lacking renewability and degradability. This has promoted the innovation and application of bio-based active packaging materials. Existing edible films are often prepared by Maillard reaction, enzymatic reaction, glutaraldehyde cross-linking and other means; Maillard reaction has problems such as high heating temperature and uncontrollable reaction products; enzymatic reaction has high cost; when glutaraldehyde cross-linking is used, there is a problem of high toxicity. The problems with the above methods limit the application of edible films in pharmaceutical and food packaging. In addition, the existing edible films have weak resistance to ultraviolet radiation and are difficult to use in food or pharmaceutical packaging that needs to be shielded from light or stored away from light. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a gelatin-mycosporine-like amino acid-dialdehyde starch composite film and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for extracting mycosporin-like amino acids from Porphyra yezoensis, comprising the following steps:

[0008] After crushing Porphyra yezoensis, adding cellulase thereto, and then adding ethanol solution with a mass concentration of 20-30%, extracting at 40-50° C. for 1-3 hours, ultrasonically extracting for 20-40 minutes, centrifuging and separating, and collecting the supernatant;

[0009] Add 2-6 times the volume of 90-97% ethanol to the supernatant, freeze the alcohol precipitation, freeze centrifuge, freeze-dry the supernatant, and the freeze-dried product is the mycosporin-like amino acid.

[0010] Mycosporine-like amino acids (MAAs) are a class of low molecular weight (<400Da) intracellular compounds, consisting of cyclohexenone or cyclohexenamine chromophores coupled to one or two amino acids responsible for UV absorption. MAAs are widely distributed in a variety of marine organisms, especially in red algae, with high molar extinction coefficients (ε = 28100-50000 L·mol -1 cm -1 ), known as the strongest UV-absorbing molecule in nature. It has the ability to absorb light in the UV-A and UV-B ranges without generating free radicals.

[0011] In some embodiments, the mass ratio of Porphyra yezoensis to cellulase is 1000:1-2.

[0012] In some embodiments, the method further includes purifying the prepared crude mycosporin-like amino acid product, and the purification method is as follows: loading the crude mycosporin-like amino acid product solution onto a Qapto Q column, and balancing the ion exchange column with ultrapure water at a flow rate of 0.5-1.5 mL / min; then linearly eluting with 0.5-1.5 moL / L NaCl elution buffer at a flow rate of 0.5-1.5 mL / min, and collecting the elution peak solution with an absorbance of 334 nm at ultraviolet absorption.

[0013] In a second aspect, the present invention provides a method for preparing a gelatin-mycosporine-like amino acid-dialdehyde starch composite film, comprising the following steps:

[0014] Add a cross-linking agent to the gelatin solution, activate it for a set time, add N-hydroxysuccinimide, and then add mycosporin-like amino acids, couple it for a set time under weak acid conditions and in the dark, to obtain Gel-MAAs;

[0015] Dissolve Gel-MAAs in water to obtain a complex solution;

[0016] Dissolving dialdehyde starch in water, gelatinizing, and adjusting to weak alkalinity to obtain a dialdehyde starch solution;

[0017] Add the dialdehyde starch solution dropwise to the complex solution, mix well, react at 35-45° C. for 1-3 hours, add 1-5% by mass glycerol, degas by ultrasonication, pour the membrane liquid into a mold, and dry to obtain the membrane.

[0018] In some embodiments, the mass ratio of the Gel-MAAs complex to the dialdehyde starch is 2-5:3;

[0019] Preferably, in the membrane solution, the content of glycerol is 3%, the content of Gel-MAAs is 4%, and the content of dialdehyde starch is 3%, where % is w / v.

[0020] In some embodiments, the pH value of the dialdehyde starch solution is 9-11, preferably 10.

[0021] In some embodiments, the cross-linking agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC).

[0022] Preferably, the mass ratio of gelatin, EDC, N-hydroxysuccinimide and mycosporin-like amino acid is 0.8-1.2:0.2-0.3:0.1-0.2:0.8-1.2.

[0023] In some embodiments, the activation time is 20-40 min.

[0024] In some embodiments, the weakly acidic pH value is 4-6, preferably 5.

[0025] In a third aspect, the present invention provides a gelatin-mycosporine-like amino acid-dialdehyde starch composite film prepared by the preparation method.

[0026] In a fourth aspect, the present invention provides the use of the gelatin-mycosporine-like amino acid-dialdehyde starch composite film in the preparation of an anti-ultraviolet device.

[0027] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0028] The microstructure of the composite film prepared by the present invention is compact, uniform, smooth and flat. The ultraviolet light blocking rate of the composite film is almost 100%. Under high-intensity ultraviolet radiation, the survival rate of the probiotics wrapped by the composite film reaches more than 70%. The cell survival rate of the composite film co-incubated with L929 cells within 24 hours was determined by CCK8 cytotoxicity experiment, and it was found that the cell survival rate of all composite film groups was more than 80%, proving that the composite film has excellent biocompatibility. At the same time, the fruit storage experiment proved that the composite film has a good effect on the appearance and color preservation of strawberries, slowed down the loss rate of substances such as pigments that are easily destroyed by ultraviolet rays, and significantly extended the shelf life of strawberries.

[0029] The gelatin grafted mycosporin-like amino acid / dialdehyde starch anti-UV composite film prepared by the casting method has excellent mechanical properties, physicochemical properties, anti-UV activity, and good biocompatibility, and has great potential in the field of active composite films.

[0030] The present invention uses dialdehyde starch to induce gelatin molecule cross-linking through Schiff base reaction, and the reaction conditions are mild. Compared with the commonly used methods such as Maillard reaction (high reaction heating temperature), enzymatic reaction (high cost), glutaraldehyde cross-linking (high cross-linking toxicity) commonly used in the preparation of edible films, this reaction has more advantages and is easy to recycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0032] Figure 1 It is a technical roadmap of an embodiment of the present invention;

[0033] Figure 2 This is a comparison chart showing the effect of cellulase amount on extraction rate;

[0034] Figure 3 This is a comparison chart of the effect of ethanol concentration on extraction rate;

[0035] Figure 4 This is a comparison chart of the effect of solid-liquid ratio on extraction rate;

[0036] Figure 5 This is a comparison chart of the effect of ultrasonic time on extraction rate;

[0037] Figure 6 is the response surface of the interaction of various factors on the extraction rate;

[0038] Figure 7 is the UV-visible spectrum analysis graph of MAAs;

[0039] Figure 8 This is the liquid chromatogram of MAAs in Porphyra yezoensis;

[0040] Fig. 9 is the liquid chromatogram of purified MAAs;

[0041] Fig.10 This is the mass spectrum of porphyra-334 in Porphyra yezoensis

[0042] Fig.11 This is the mass spectrum of shinorine in Porphyra yezoensis;

[0043] Fig.12 This is a comparison of the cytotoxicity results of MAAs on L-929 cells;

[0044] Fig.13 is the live / dead staining image of cells cultured with different concentrations of MAAs medium for 1 day;

[0045] Fig.14 It is a schematic diagram of the synthesis route of Gel-Dopa;

[0046] Fig.15 is the infrared spectra of Gel and Gel-MAAs;

[0047] Fig.16 is the MAAs standard curve;

[0048] Fig.17 It is the UV scanning spectrum of Gel, MAAs and Gel-MAAs complex;

[0049] Fig.18 is the circular dichroism spectra of Gel and Gel-MAAs;

[0050] Fig.19 is the XRD spectrum of Gel-MAAs composite;

[0051] Fig. 20 This is the docking result diagram of Porphyra-334 and collagen fragment;

[0052] Fig.21 This is the docking result diagram of Shinorine and collagen fragment;

[0053] Fig. 22 is the microscopic morphology of Gel-MAAs / DS composite membrane;

[0054] Fig.23 is the thermogravimetric analysis graph of Gel-MAAs / DS composite membrane;

[0055] Fig.24 is a comparison chart of the tensile strength of Gel-MAAs / DS composite membranes;

[0056] Fig.25 is a comparison chart of elongation at break of Gel-MAAs / DS composite membrane;

[0057] Fig.26 It is a comparison chart of water absorption of Gel-MAAs / DS composite membrane;

[0058] Fig. 27 It is a comparison chart of water solubility of Gel-MAAs / DS composite membrane;

[0059] Fig.28 This is a comparison chart of water vapor permeability of Gel-MAAs / DS composite films;

[0060] Fig.29 This is a comparison of the water contact angles of the Gel-MAAs / DS composite membrane;

[0061] Fig.30is the light transmittance of the Gel-MAAs / DS composite film;

[0062] Fig.31 This is a comparison chart of the UV protection of probiotics by Gel-MAAs / DS composite membrane;

[0063] Fig.32 This is a comparison chart of the viability of probiotics under UV protection by Gel-MAAs / DS composite membrane;

[0064] Fig.33 These are photos of strawberries stored at 4°C under different conditions;

[0065] Fig.34 This is a comparison chart of the weight loss rate of strawberries at 4°C under different conditions;

[0066] Fig.35 This is a comparison chart of the cytotoxicity results of the composite membrane on L-929 cells;

[0067] Fig.36 This is a live / dead staining image of cells cultured with the extract for 1 day. DETAILED DESCRIPTION

[0068] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0069] Example

[0070] 1) Optimization of conditions for extracting MAAs from Porphyra yezoensis using cellulase

[0071] Mouse connective tissue L cell line 929 was obtained from the cell bank of Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences. It was stably cultured, passaged and cryopreserved in Room 206 of the Science Laboratory Building, College of Oceanography, Shandong University.

[0072] Table 1 Experimental materials and reagents

[0073]

[0074] Table 2 Experimental instruments and equipment

[0075]

[0076]

[0077] The method for extracting MAAs from Porphyra yezoensis by cellulase is as follows:

[0078] Crush Porphyra yezoensis to 60 mesh and collect Porphyra powder → add 0.002g cellulase to 2g Porphyra powder and then add 60mL 25% ethanol solution → extract in 45℃ water bath for 2h → ultrasonic extraction for 30min → centrifuge at 5000r / min for 30min → collect supernatant → add 4 times volume of 95% ethanol to supernatant → freeze and precipitate overnight at -20℃ → freeze and centrifuge at 5000r / min for 30min → rotary evaporate the supernatant at 45℃ to the bottom of a bottle → freeze-dry and collect the sample.

[0079] The main factors affecting the extraction rate of MAAs from Porphyra yezoensis are ultrasonic time, ethanol concentration, liquid-to-solid ratio, and cellulase quality. Extraction tests were conducted on these four single factor variables. The extraction factor conditions were designed as follows:

[0080] Ultrasonication time (min): 0, 10, 20, 30, 40;

[0081] Ethanol concentration (%): 10, 15, 20, 25, 30;

[0082] Solid-liquid ratio (g / mL): 1:20, 1:25, 1:30, 1:35, 1:40;

[0083] Cellulase mass (g / g): 0, 0.001, 0.002, 0.003, 0.004.

[0084] When one of the single factor parameters was changed, the other factor parameters were set as ultrasonic time 30 min, ethanol concentration 15%, solid-liquid ratio 1:30 g / mL, and cellulase mass 0.002 g.

[0085] Response surface optimization experiment

[0086] Comprehensive single-factor experiments were conducted to determine the appropriate range of each factor. Since there was no significant difference in the effect of ultrasonic time on the extraction efficiency of MAAs, the three factors of cellulase amount, ethanol concentration and liquid-to-solid ratio were finally investigated. The Box-Behnken Designs experimental design was adopted, and the MAAs extraction rate in Porphyra yezoensis was used as the response value to further optimize the optimal conditions for the MAAs extraction process. The factor levels are shown in Table 3.

[0087] Table 3 Experimental factor level table

[0088]

[0089] Purification steps of MAAs from Porphyra yezoensis:

[0090] A crude MAAs sample was dissolved in ultrapure water to obtain a crude MAAs extract (1 g / mL), which was loaded onto a Qapto Q column at 1.0 mL / min. The ion exchange column was balanced and stabilized using an equilibrium buffer (ultrapure water, pH 7.5) at a flow rate of 1.0 mL / min. A 1 moL / L NaCl elution buffer was used for linear elution at a flow rate of 1.0 mL / min, and the elution peak solution with UV absorption at 334 nm absorbance was collected.

[0091] UV-Vis absorption spectrum scanning

[0092] Take a small amount of freeze-dried MAAs and dissolve it in ultrapure water to make up to volume (0.002 g / mL). Scan the absorption spectrum with a UV-visible spectrophotometer to determine the spectrum of the sample at 200-500 nm.

[0093] HPLC

[0094] Dissolve the freeze-dried MAAs powder in ultrapure water and adjust the volume to 0.005 g / mL, filter through a 0.22 μm inorganic filter membrane, and transfer the membrane solution to a liquid phase vial. Establish a liquid chromatography detection method: chromatographic column Bischoff-ProntoSIL-120-5-C 18 AQ plus (4.6×250mm, 5μm), phase A: 0.2% formic acid, phase B: chromatographic grade methanol (A:B=1:9), flow rate 1ml / min, column temperature 25°C, injection volume 10μL, analysis time 10min.

[0095] LC-MS analysis

[0096] Dissolve the freeze-dried MAAs powder in ultrapure water and adjust the volume to 0.005 g / mL. After passing through the membrane, place it in a liquid phase vial and use liquid chromatography-mass spectrometry to analyze the molecular weight of MAAs contained in the sample. Liquid phase conditions: Chromatographic column Aglient poroshell 120SB-C 18 (3.0×150mm) Phase A: 0.2% formic acid in water, Phase B: mass spectrometry grade methanol, elution time 15min, injection volume 10μL, column temperature 25℃, flow rate 1mL / min. Mass spectrometry conditions: negative ionization mode, spray pressure 45psi, dry gas flow (N2) flow rate 10L / min. Dry gas temperature 350℃, capillary voltage 4500V.

[0097] Biocompatibility verification

[0098] The cytotoxicity of MAAs was detected by CCK8 assay and live / dead cell staining.

[0099] In the first step, MAAs were dissolved in culture medium and diluted to concentrations of 5, 2.5, 1.25, 0.625, 0.32, 0.16, and 0.08 mg / mL, and sterilized by membrane for later use.

[0100] In the second step, mouse fibroblasts (L929) were revived and transplanted into DMEM medium containing 10% fetal bovine serum and 1% double antibody. Then, L929 cells in the logarithmic growth phase were digested with EDTA-containing trypsin and diluted with new medium to obtain 5×10 5 Add 100 μL of cell suspension to each well of a 96-well cell culture plate to make the cell seeding density 1×10 4 The cells were placed in a 37°C incubator and incubated for 24 h.

[0101] The third step is to observe that the cells are fully grown under a microscope, and then use a pipette to remove the culture medium from the 96-well plate, add 100 μL of MAAs culture medium and 100 μL of culture medium to the experimental group and the blank group, and continue to incubate in a 37°C cell culture incubator for 24 hours. After 24 hours, remove the culture medium and wash the suspended cells with PBS solution, add 100 μL of CCK-8 solution (diluted ten times with culture medium) to each well, and continue to incubate in a 37°C incubator for 1 hour, then detect the absorbance at a wavelength of 570 nm and calculate the cell survival rate:

[0102]

[0103] Among them, A t is the absorbance of the cell culture wells with MAAs culture medium added, A0 is the absorbance of the culture wells with DMEM culture medium, and A e is the absorbance of the untreated cell group.

[0104] Live / dead cell staining assay: Take 1 mL of cells at a density of 6 × 10 4 Cells were placed in a 24-well plate at a concentration of 1 cell / mL. After incubation in an incubator for 1 day, the upper culture medium was aspirated, and 1 mL of MAAs culture solution and fresh culture medium were added to the 24-well plate for the experimental group and the blank group, respectively, and the plate was placed in a 37°C constant temperature incubator for another day. The culture medium was removed, the remaining culture medium was washed with PBS, 250 μL of AO / EB reagent was added for staining for 15 minutes, and the experimental results were observed with an inverted fluorescence microscope.

[0105] The above experimental results were analyzed by GraphPad Prism 9.0 software and Origin 2022 software for data analysis, statistical analysis and image processing. The quantitative data were expressed as mean ± standard deviation (Mean ± SD), and ANOVA was used to analyze the differences between the data of each group, where *p < 0.05, **p < 0.01, ***p < 0.001, ****p < 0.0001, * was considered to be significantly different, and ns indicated no significant difference.

[0106] Experimental results analysis

[0107] Effect of Cellulase Amount on Extraction Rate

[0108] Under the conditions of 15% ethanol concentration, 30 min ultrasonic extraction time and 1:30 (g / mL) liquid-to-solid ratio, when the mass of cellulase changes from 0 to 0.004 g / g, the extraction rate basically increases and then decreases. When the amount of cellulase added is 0.001 (g / g), the extraction rate is the largest. Figure 2 It can be seen that when the amount of cellulase exceeds a certain range, the cell survival rate will decrease. Therefore, the cellulase concentration range selected in the subsequent optimization experiment is preferably 0.001-0.003g / g.

[0109] Effect of ethanol concentration on extraction rate

[0110] Under the conditions of ultrasonic extraction time of 30 min, liquid-to-solid ratio of 1:30 (g / mL), and cellulase mass of 0.002 (g / g), when the ethanol concentration changed from 10% to 30%, the extraction rate basically showed an upward and then downward trend. As the ethanol concentration increased from 15% to 30%, the extraction rate showed a downward trend instead. Figure 3 It may be because the reduction of polar water molecules affects the state of agar in laver and hinders the dissolution of MAAs, so the ethanol concentration range of 15-25% is appropriate for subsequent optimization experiments.

[0111] Effect of solid-liquid ratio on extraction rate

[0112] Under the conditions of ethanol concentration of 15%, ultrasonic extraction time of 30min, and cellulase mass of 0.002 (g / g), it can be seen from the experimental data that with the continuous increase of liquid-to-solid ratio, the extraction rate value shows a trend of increasing and then decreasing, and reaches the highest value when the liquid-to-solid ratio is 1:30 (g / mL). The reason for the analysis of the experiment may be that when the liquid-to-solid ratio is low, the solvent and the laver powder cannot fully infiltrate and contact, and the laver is rich in polysaccharides, and the laver powder has strong water absorption, which affects the extraction of MAAs. When the liquid-to-solid ratio reaches about 1:30 (g / mL), the laver powder absorbs water to saturation, which is conducive to the dissolution of MAAs. As the liquid-to-solid ratio increases further, the amount of ethanol in the system also increases. Under the action of ultrasonic and thermal effects, polar MAAs molecules may be decomposed or converted, and when the solvent is too high, the subsequent extraction process will increase the loss. Therefore, it is appropriate to select a liquid-to-solid ratio of 1:25~1:35 (g / mL). Figure 4 shown.

[0113] Effect of ultrasonic time on extraction rate

[0114] Under the conditions of ethanol concentration of 15%, liquid-to-solid ratio of 1:30 (g / mL), and cellulase mass of 0.002 (g / g), when the ultrasonic time varied from 0 to 40 min, the extraction rate reached the highest value when the ultrasonic time was 20 min. Figure 5 However, there was no significant difference among the groups, which means that the ultrasonic time had little effect on the extraction efficiency of MAAs, so 20 min with a relatively higher extraction rate was finally selected as the reaction condition.

[0115] Results of response surface optimization experiment on MAAs extraction rate

[0116] Taking into account the single factor experimental results, cost and extraction efficiency, the optimal level range of each factor was finally determined. At the same time, according to the Box-Behnken Designs design principle, the amount of cellulase (A), ethanol concentration (B), and solid-liquid ratio (C) were determined as independent variables, and the MAAs extraction efficiency was used as the response value to design a response surface experiment. The experimental plan and results are shown in Table 4.

[0117] Table 4 Response surface experiment scheme and results

[0118]

[0119] The experimental data in Table 2-4 were fitted with regression analysis, and the model was subjected to variance analysis and significance test. The response surface regression model finally established was:

[0120] Y=11.98+0.41A+0.36B+0.28C-0.24AB-0.44AC+0.012BC-1.57A 2-1.60B 2 -1.02C 2 .

[0121] The regression of this response surface model was significant (p < 0.01), and the lack of fit term was not significant (p > 0.05). The lack of fit term means that the regression equation can well reflect the relationship between each factor and the response value, indicating that this response surface regression model can be used to analyze and predict the extraction rate of MAAs in Porphyra yezoensis by ultrasonic cellulase method (Table 5).

[0122] Table 5 Regression and variance analysis results

[0123]

[0124] Note: **, extremely significant (p<0.01), *, significant (p<0.05).

[0125] The influence of each variable in the regression equation on the response value is determined by the F test. The smaller the P and the larger the F, the higher the significance of the corresponding variable. 2 , B 2 , C 2 and AC have significant effects on the response value (p < 0.05). From the overall experimental data, the first and second terms have the most significant effects, followed by the interaction term. According to the size of F, the order of the factors affecting the extraction efficiency is cellulase amount > ethanol concentration > liquid-to-solid ratio.

[0126] Design-Expert software was used to process and plot the experimental results, as shown in the following figure. Figure 6 The interaction of the two factors on the response value can be reflected from the three-dimensional surface plot. From the existence of the highest point on the response surface, it can be understood that there are extreme values ​​in the range selected by the experiment.

[0127] The strength of the interaction effect can be seen from the shape of the fitted response surface and the shape of the contour lines. The curvature of the surface reflects the influence of a single factor on the response value. It can be observed from the response surface diagram that the influence of cellulase quality on the response value is greater than that of liquid-to-solid ratio and ethanol concentration on the response value. Specifically, the curve of the graph surface is steeper, which is consistent with the results of linear regression analysis. If the center of the contour line is an ellipse, it means that the interaction term of the two factors has an obvious effect, while a circle is not obvious. Figure 6 The middle high line graph shows that the interaction between ethanol concentration and cellulase quality is the most obvious, and the interaction between ethanol concentration and liquid-to-solid ratio is the least obvious. This is consistent with the results of regression analysis.

[0128] The results of the Design-Expert software fitting showed that the extraction conditions with the highest extraction rate were as follows: when the amount of cellulase was 1.11 mg·g -1, ethanol concentration is 15.53%, and the maximum extraction rate is 12.0368% when the solid-liquid ratio is 1:31.

[0129] UV scanning spectrum

[0130] UV-Visible spectroscopy analysis of extracts from Porphyra yezoensis Figure 7 It can be seen that the extract shows the highest absorption peak at 334nm. Based on the comprehensive references, it is preliminarily inferred that Porphyra yezoensis contains MAAs.

[0131] HPLC

[0132] By liquid chromatography Figure 8 It can be seen that there are 6 peaks in the chromatogram, including 2 main peaks and 4 minor peaks, indicating that there are at least 6 MAAs in Porphyra yezoensis, but there are 2 main components, with normalized peak areas of 9.11% and 84.28%. Fig. 9 It can be seen that the purified MAAs have two main peaks, proving that there are still two kinds of MAAs components in the purified MAAs. The normalized peak area of ​​the chromatographic peak with a retention time of 4.6 min is 33.89%, while the normalized peak area of ​​the chromatographic peak with a retention time of 8.9 min is 66.11%, and its maximum ultraviolet absorption wavelength λmax is 334 nm.

[0133] LC-MS analysis results

[0134] LC-MS detection can obtain the mass spectrometric structure of the main components of MAAs in Porphyra yezoensis, see Fig.10 , the main component ion peak [M+H] - m / z = 345, with an estimated molecular weight of 346. Fig.11 , the main component ion peak [M+H] - m / z=331, and the estimated molecular weight is 332.

[0135] Based on the comprehensive analysis of HPLC, UV and LC-MS spectra and combined with references, the main components of MAAs extract from Porphyra yezoensis were determined to be porphyra-334 and shinorine.

[0136] Biocompatibility validation results of MAAs

[0137] The cytotoxicity of MAAs is also one of the important indicators for evaluating them as active additives. The CCK8 method was used to detect the cytotoxicity of MAAs solutions on L-929 cells. The MAAs concentration ranged from 5 mg / mL to 0.08 mg / mL, and the reaction time was 24 h. Fig.12As shown in the figure, MAAs can significantly promote cell growth at lower concentrations, but at high concentrations, MAAs will have a slight inhibitory effect on cells, and the cytotoxicity is dose-dependent. When the concentration of MAAs is as high as 5 mg / mL, the cell survival rate is still higher than 90%. The experimental results show that MAAs have good biocompatibility.

[0138] from Fig.13 The results of live / dead cell staining assay were consistent with those of CCK8. After 24 hours of co-incubation of L929 cells with MAAs medium, the vast majority of L929 cells maintained spindle-shaped morphology and were evenly distributed and green living cells, with basically no red blood cells and dead cells, indicating that MAAs had no cytotoxicity and had good biocompatibility.

[0139] 2) Preparation of Gel-MAAs

[0140] Table 6 Experimental materials and reagents

[0141]

[0142] Table 7 Experimental instruments and equipment

[0143]

[0144] The preparation method of Gel-MAAs complex is as follows: weigh 1g gelatin (Gel) and dissolve it in 100mL deionized water and stir it at 60°C for 30min to completely dissolve it. After cooling to room temperature, add 0.25g EDC and keep stirring until it is completely dissolved. After activation for half an hour, add 0.15g NHS. Then add 1g MAAs to the activated solution, and couple it for 3h in dark conditions at pH 5 and room temperature under continuous stirring. After the reaction is completed, dialyze it using a dialysis bag with a cutoff of 12000-14000Da, and dialyze it in low-temperature deionized water acidified with hydrochloric acid at pH 5 (frequently changed) for 72h. After waiting for the dialysis to end, freeze-dry the dialyzed solution to finally obtain the product Gel-MAAs. Fig.14 shown.

[0145] Fourier transform infrared spectroscopy

[0146] Take appropriate amount of Gel and Gel-MAAs and dry potassium bromide powder (1:100), mix and grind them evenly, press them into thin slices, and scan them in the full band with infrared. The scanning range of the spectrum is 4000-400cm -1 , resolution 4cm -1 . Origin 2022 software was used for drawing.

[0147] Construction of MAAs standard curve:

[0148] Drawing of MAAs standard curve: MAAs are prepared into 10 mg / mL stock solution, diluted in sequence, and subjected to UV spectrophotometric detection to determine the maximum absorption peak position of MAAs. The absorbance of the MAAs solution at the maximum absorption peak is recorded, and finally the concentration of MAAs is used as the horizontal axis and the absorbance is used as the vertical axis to draw a standard curve.

[0149] Gel-MAAs grafting rate determination:

[0150] Gel-MAAs grafting rate determination: accurately prepare the Gel and Gel-MAAs complex standard solution (0.002 mg / mL), and then use the UV spectrophotometer to scan the UV spectrum at 200-500 nm to obtain the UV spectrum of the Gel and Gel-MAAs complex. At the same time, determine the maximum absorption wavelength of Gel-MAAs, measure the absorbance of Gel-MAAs at the highest absorption peak, and calculate the grafting rate of MAAs based on the obtained MAAs standard curve.

[0151] Circular dichroism spectral scanning

[0152] Gel and Gel-MAAs were accurately weighed and prepared into dilute solutions (0.125 mg / mL), and the prepared samples were subjected to spectral scanning at 190-280 nm using a circular dichroism spectrometer (Chirascan, Applied Photophysics, UK).

[0153] X-ray diffraction analysis

[0154] The crystal structure of Gel and the prepared Gel-MAAs complex was studied by X-ray diffraction tester (D8, Bruker, Germany). The sample measurement conditions were: diffraction width DS = SS = 1°, step length 0.02°, step speed 6° / min, RS = 0.3 mm, 20°C, 40 kV, 40 mA, scanning angle (2θ) range 5-85°, and the spectra of the samples were analyzed and processed by MDI Jade software.

[0155] Molecular docking-data and simulation software

[0156] The structure of gelatin was obtained and downloaded from the RCSB PDB protein database (http: / / www.rcsb.org / pdb / home / home.do) (PDBID: 8h0e). The spatial structures of MAAs were obtained from the Protein Data Bank (https: / / pubchem.ncbi.nlm.nih.gov / ), with Porphyra-334 (PubChem CID6857486) and Shinorine (PubChem CID10471931) as representatives. The Schrodinger software package was used for molecular covalent docking. Unless otherwise specified, the default parameter settings were used.

[0157] Molecular docking process: The gelatin structure was prepared using the Protein Preparation Wizard module in the Schrodinger software package: protein hydrogenation, removal of water molecules, assignment of the OPLS-2005 force field and energy optimization of the protein structure, and deletion of all docked small molecules in the gelatin structure.

[0158] LigPrep module was used for ligand preparation: OPLS-2005 force field was assigned to generate structural tautomers of each small molecule at pH = 7.0 ± 2.0, and the corresponding reasonable 3D structure of each small molecule was generated.

[0159] Covalent docking calculations were performed using the CovDock module in the Schrodinger software package: first, the active pocket was defined with the ligand of each crystal structure as the center, with the initial X, Y, and Z dimensions of 126×126×126 points, respectively. Once the most favorable interaction site for each formed complex was determined, a small grid box of 40×40×40 points was used to specify their respective binding energies. Lys12 was then used as the reaction site for covalent docking, and the docking reaction was selected as Iminecondensation, with the remaining parameters set to default.

[0160] The docking results were ranked according to the docking scores, and the advantageous docking conformations were screened out and exported for analysis.

[0161] The above experimental results were analyzed by GraphPad Prism 9.0 software and Origin 2022 software for data analysis, statistical analysis and image processing. The quantitative data were expressed as mean ± standard deviation (Mean ± SD), and ANOVA was used to analyze the differences between the data of each group, where *p < 0.05, **p < 0.01, ***p < 0.001, ****p < 0.0001, asterisks were considered to be significantly different, and ns indicated no significant difference.

[0162] Results and Discussion

[0163] Fourier transform infrared spectroscopy

[0164] The carboxylate groups of MAAs and the amino groups of gelatin are coupled by EDC / NHS to form amide bonds. Fig.15 As shown in the figure, by comparing the infrared spectra of Gel and Gel-MAAs complex, it can be seen that the main characteristic peaks of Gel-MAAs complex are consistent with the main characteristic peaks of Gel, indicating that the grafting of MAAs does not affect the overall structure of Gel. In addition, in the spectrum of Gel-MAAs complex, at 1451cm -1 and 2921cm -1 The characteristic absorption peaks attributable to MAAs molecules appeared; 1636cm -1 The amide peak appears at , which belongs to the stretching vibration of the NC=O bond of the amide group and has a higher intensity, proving that the amidation reaction occurs and the Gel-MAAs grafting is successful.

[0165] MAAs standard curve and UV spectrum

[0166] With MAAs concentration as the horizontal axis and absorbance as the vertical axis, a standard curve of MAAs was successfully obtained, as shown in Fig.16 As shown. Fig.17 As shown in the figure, the highest absorption peak of MAAs appears at 334nm, Gel does not show an obvious ultraviolet absorption peak at 334nm, and the highest peak of the Gel-MAAs complex also appears at 334nm, which shows that MAAs are successfully grafted onto the Gel molecule. Substituting the absorbance of the Gel-MAAs complex into the standard curve, the content of MAAs in the Gel-MAAs complex can be calculated to be (148.06±3.79)μmol / g.

[0167] Circular dichroism spectrum

[0168] The changes in protein secondary structure can be determined by circular dichroism, which is the most widely used method. In this example, the changes in circular dichroism are used to study the effects of modified grafting of MAAs on the secondary structure of Gel molecules. Fig.18 As shown in the figure, a more obvious negative peak can be observed at 198nm in the Gel spectrum, which is due to the typical random coil conformation of Gel. At the same time, the band ellipticity band of the Gel-MAAs complex near 200nm increases significantly, which is mainly due to the increase in random coil conformation.

[0169] X-ray diffraction

[0170] The crystallinity of polymers can be detected by X-ray diffraction. Sharp and narrow peaks are the characteristics of crystals, while broad and diffuse diffraction peaks are exhibited by amorphous states. Fig.19 As shown, Gel has a broad peak near 2θ==20.7°, indicating its amorphous structure. The diffraction peak intensity of the Gel-MAAs complex is significantly reduced, indicating that its amorphous state is more significant and the amidation reaction reduces the crystallinity of Gel.

[0171] Molecular docking results

[0172] The covalent docking mechanism was analyzed by Schrodinger Maestro 12.8 software, and docking was performed between Porphyra-334, Shinorine and collagen fragments. The results showed the results of covalent docking of MAAs in the selected area with Lys-12 of the collagen fragment. The covalent docking mechanism was analyzed by Schrodinger Maestro12.8 software for scoring, namely Docking score, the smaller the value, the easier it is to bind to the collagen fragment. The prediction results showed that the Docking score of Porphyra-334 and the collagen fragment was -3.742, and the Docking score of Shinorine and the collagen fragment was -3.811, indicating that MAAs have strong binding ability with the collagen fragment, and the Shinorine configuration has stronger binding ability.

[0173] Table 8 Results derived after docking screening between Porphyra-334, Shinorine and collagen fragments

[0174]

[0175] 3) Preparation of Gel-MAAs / DS composite membrane

[0176] Table 9 Experimental materials and reagents

[0177]

[0178] Table 10 Experimental instruments and equipment

[0179]

[0180]

[0181] Preparation of Gel-MAAs / DS composite membrane:

[0182] Weigh 2, 3, 4, and 5 g of Gel-MAAs complex respectively and dissolve them in 50 ml of deionized water, and stir at 60°C for 0.5 h to completely dissolve them. Weigh another 3 g of dialdehyde starch and dissolve it in 50 ml of deionized water and fully gelatinize (3%), and adjust the pH value to about 10. Slowly add the dialdehyde starch solution dropwise into the gelatin solution, stir to mix evenly, react at 40°C for 1.5 h, and add 3% glycerol as a plasticizer. After ultrasonic degassing, pour 20 g of the membrane liquid into a plastic culture dish with a diameter of 90 mm and place it in a constant temperature forced air drying oven at 30°C to dry. Place the membrane in a drying dish (RH 60%, room temperature) filled with saturated KBr solution to rewet it, and take it out for observation after 24 hours.

[0183] SEM morphology analysis of Gel-MAAs / DS composite membrane

[0184] The film samples were broken in liquid nitrogen and mounted on a sample holder using double-sided tape. Then, the film samples were sputtered with gold using a sputter coater. The film samples were observed by field emission scanning electron microscopy with an accelerating beam voltage of 20 kV.

[0185] Thermogravimetric analysis of Gel-MAAs / DS composite membrane

[0186] The sample was weighed with an electronic analytical balance and placed in a crucible. Under N2 protection, the thermal weight loss curve was recorded within the temperature range. The mass change of the sample was determined by thermogravimetric analysis (TGA).

[0187] Mechanical properties of Gel-MAAs / DS composite membranes

[0188] The composite film was cut into 40×10mm rectangular strips and clamped flat on the tensile probe of the texture analyzer at both ends. The initial spacing was set to 10mm and the tensile speed was set to 60mm / min. Three parallel experiments were conducted on each layer of the composite film, and the maximum tensile force and elongation of the film at break were recorded, and the results were averaged.

[0189] Tensile strength(MPa)=F÷(d×W)#(4-1)

[0190] Elongationat break(%)=ΔL÷L0#(4-2);

[0191] Wherein, F is the film fracture stress (N), d is the film thickness (mm), W is the film width (mm); ΔL and L0 are the stretched length and original length (mm) of the film sample, respectively.

[0192] Water absorption and water solubility of Gel-MAAs / DS composite membrane

[0193] The long-term water absorption and water solubility of the film are determined by the water absorption (Wa ) and water solubility (W s The composite film was cut into square pieces of 2×2 cm and dried in an oven at 105°C for 24 h. The initial dry weight (W o ), then transferred to 50 mL of distilled water at room temperature and soaked for 24 h, then taken out of the water and wiped dry with filter paper, and recorded as wet weight (W t Finally, the sample was placed in a 105°C oven for 24 h and transferred to a dryer for cooling. The film dry weight (W d ).

[0194] W a (%)=(W t -W0)÷W0×100%#(4-3);

[0195] W s (%) = (W0-W d )÷W0×100%#(4-4).

[0196] Water vapor permeability of Gel-MAAs / DS composite membrane

[0197] Weigh 3 g of anhydrous CaCl2 into a 50 mm x 10 mm weighing bottle. Cover the mouth of the bottle with an intact film (diameter: 30 mm) and seal it with vaseline. Record the initial mass of the weighing bottle. Place them in a desiccator containing a saturated NaCl solution (60% RH) at room temperature. Measure the mass of the weighing bottle every 24 hours for 3 consecutive days.

[0198] WVP=(24×Δm)÷At#(4-5).

[0199] Where WVP is the water vapor transmission rate (g / (m 2 ·24h)); A is the film area through which water vapor can pass (m 2 ), t is the time interval between two mass increments after stabilization (h), and Δm is the mass increase after moisture absorption (g).

[0200] Water contact angle of Gel-MAAs / DS composite film

[0201] The optical contact angle meter is used to detect the hydrophilicity of the composite film: 1 μL of ultrapure water is placed on the sample, and then the state of the water drop on the film surface is photographed 3s after the water is dripped at ambient temperature to measure the water contact angle. The initial contact between the water drop and the surface is calculated by software to obtain the water contact angle value on the film surface. All experiments were performed 3 times for each sample.

[0202] Light transmittance of Gel-MAAs / DS composite film

[0203] Cut the composite film into 1×4cm pieces of a certain thickness2 The composite film was scanned in the 200-800nm ​​band using a UV-visible spectrophotometer. The UV-visible spectrum was used to test the transmittance of the film material in the ultraviolet and visible regions.

[0204] Study on the Anti-ultraviolet Performance of Gel-MAAs / DS Composite Film-Verification of the Protective Effect on Probiotics

[0205] Lactobacillus rhamnosus was used to verify the protective effect of the composite film on probiotics under ultraviolet light.

[0206] First, prepare MRS solid culture medium and liquid culture medium. Preparation of solid culture medium: weigh 33.6g of MRS agar powder and dissolve it in 500mL of deionized water. After sterilization, transfer it to the super workbench. When the culture medium cools to a slightly hot temperature, pour it into a 9cm diameter sterile culture dish for standby use. After solidification, store it upside down. Preparation of MRS liquid culture medium: weigh 26.1g of MRS broth powder and dissolve it in 500mL of deionized water. After sterilization for 20 minutes, cool it for standby use.

[0207] The concentration was prepared to be 1×10 6 The bacterial suspension of CFU / mL was continuously diluted with sterile saline and transferred to a sterile culture dish, covered with a composite film and irradiated under a UV lamp for 15 minutes. 200 μL of the irradiated bacterial solution was evenly spread on the MRS solid culture medium and cultured at 37°C for 48 hours. The bacterial solution without film and the bacterial solution covered with PE film were used as controls to observe and record the number of probiotic colonies.

[0208] C=B÷A×100%#(4-6).

[0209] C is the survival rate of probiotics, A is the colony count of the group without UV irradiation, and B is the colony count of the experimental group.

[0210] Verification of strawberry preservation by Gel-MAAs / DS composite film

[0211] Strawberries (purchased from the local market) were divided into three groups. The control group was not covered and the group was covered with PE plastic wrap, and the experimental group was sealed with the prepared Gel-MAAs / DS composite film. They were placed in a refrigerator at 4°C and photographed every 24 hours to observe the deterioration of the strawberries. The weight of the strawberries was weighed at the same time to calculate the weight loss rate.

[0212] Biocompatibility verification of Gel-MAAs / DS composite membrane

[0213] 1 g of the composite film was sterilized in 70% ethanol for 2 hours and washed three times in sterile phosphate buffered saline (PBS) for 10 minutes each time. Each sterilized film was cultured in 10 mL of complete culture medium at 37°C for 24 hours and the extract was collected by centrifugation; the specific experimental method is as above.

[0214] The above experimental results were analyzed by GraphPad Prism 9.0 software and Origin 2022 software for data analysis, statistical analysis and image processing. The quantitative data were expressed as mean ± standard deviation (Mean ± SD), and ANOVA was used to analyze the differences between the data of each group, where *p < 0.05, **p < 0.01, ***p < 0.001, ****p < 0.0001, asterisks were considered to be significantly different, and ns indicated no significant difference.

[0215] Results and Discussion

[0216] SEM results of Gel-MAAs / DS composite membrane

[0217] The freeze-dried films were fractured with liquid nitrogen to observe the microscopic morphology of the surface and cross section. All films showed a dense and smooth surface, indicating that the polymers (Gel-MAAs and DS) were fully mixed to form a compatible film. As the content of Gel-MAAs increased, the surface of the cross-linked film still showed a flat and dense microstructure, and no phase separation or polymer aggregation was observed. Fig. 22 These results indicate that the introduction of Schiff-base networks and the establishment of hydrogen bonding interactions improve the compatibility between components, thereby increasing the crosslinking density and uniformity. The covalent and non-covalent interactions formed significantly changed the microstructure of the film, which also provided evidence for the effect of Gel-MAAs content on the mechanical and barrier properties of the film.

[0218] Thermogravimetric analysis results of Gel-MAAs / DS composite membrane

[0219] from Fig.23 It can be observed that the composite film shows three stages of heat loss. The first stage is mainly from room temperature to 200°C, and the mass loss is mainly due to the loss of low molecular weight substances such as water and volatile substances in the sample; the second stage is mainly from 250 to 500°C, which is mainly caused by the volatilization of glycerol in the film and the thermal degradation of gelatin molecular chains and DAS macromolecular chains. The thermal degradation is the main weight loss stage; when the temperature reaches 600°C, the remaining mass is 28.7%.

[0220] Mechanical properties of Gel-MAAs / DS composite membranes

[0221] Mechanical properties are very important for films to protect the integrity of the product. Fig.24 and Fig.25 The mechanical properties of Gel-MAAs / DS composite membrane are shown. Fig.24 It can be observed that as the concentration of the Gel-MAAs complex increases, the tensile strength of the composite mold increases first and then decreases. The reason for the change may be that when the content of the Gel-MAAs complex is low, it can only be insufficiently cross-linked with DS, resulting in stress concentration and reduced tensile strength. And DS, as a hydrophilic natural cross-linker, will also cause the above phenomenon due to its own plasticizing effect and hydrophilicity; when the content of the Gel-MAAs complex is high, DS is insufficient to fully cross-link with Gel-MAAs, resulting in reduced strength of the membrane. After adding 4% Gel-MAAs to DS, the tensile strength reached 5.8MPa and the tensile strength reached the highest due to relatively sufficient cross-linking between DS and Gel-MAAs. These results are closely related to the stronger cross-linking within the polymer component. The elongation at break gradually decreases with the increase of the concentration of the Gel-MAAs complex. The introduction of Schiff base bonds and hydrogen bond interactions enhances the mechanical properties of the film. The Schiff base cross-linking structure enhances the intermolecular forces, thereby forming a denser and more compact network structure. This change restricts the movement of molecular chains and reduces their elongation ability.

[0222] Water absorption and water solubility of Gel-MAAs / DS composite membrane

[0223] The water absorption and water solubility of the composite membrane are as follows Fig.26 and Fig. 27 As shown in the figure, as the concentration of Gel-MAAs complex increases, the water absorption and water solubility of the composite film increase-decrease-increase. This may be because the degree of cross-linking with DA increases first and then decreases with the increase of Gel-MAAs concentration. 2% and 3% Gel-MAAs are not enough to fully cross-link with DS, and the hydrophilicity of DS leads to increased water absorption and water solubility of the composite film; 4% Gel-MAAs has the best cross-linking degree with DS, forming a denser and more compact network structure, so the water absorption and water solubility of the composite film decrease. 5% Gel-MAAs is too much, and gelatin contains hydrophilic amino and carboxyl groups, which agrees to increase the water absorption and water solubility of the composite film. This result is consistent with the inference of mechanical properties.

[0224] Water vapor permeability and water contact angle of Gel-MAAs / DS composite membrane

[0225] Water vapor in the environment can promote the growth of microorganisms and directly affect the freshness of materials during the preservation process. WVP is an important indicator for evaluating the applicability of cling film, reflecting the ability of the composite film to block water vapor. Hydrophobicity is the most important factor in determining the applicability of polymer film materials. The hydrophobicity of the film is determined by Fig.29The static water contact angle in the sample is evaluated. The barrier ability of the material is mainly affected by the chemical structure and microstructure.

[0226] Compared with other films, the structure of 4% Gel-MAAs / DS composite film is denser and smoother, which improves the hydrophobicity of the film and enhances its resistance to water vapor. Fig.28 As shown. These results demonstrate the compactness and integrity of the Gel-MAAs / DS composite membrane. The Gel-MAAs / DS composite membrane forms a compact structure between DS and Gel-MAAs through the Schiff base, which produces a strong intermolecular force and has excellent barrier properties, and is expected to be used in active composite membrane materials.

[0227] Light transmittance of Gel-MAAs / DS composite film

[0228] Depend on Fig.30 It can be seen that the control film has a higher transmittance (37-42% at 280-400nm) and the commercially available PE film has a high transmittance, indicating that they cannot shield food from UV radiation and are difficult to prevent UV-induced oxidation. It is worth noting that the transmittance of the Gel-MAAs / DS composite film within the UV spectrum (200–400nm) is almost 0, showing excellent anti-UV performance.

[0229] Protective effect of Gel-MAAs / DS composite film on probiotics under ultraviolet light

[0230] In modern life, people have a stronger demand for probiotics, and probiotics are added to many foods, medicines and health products. Ultraviolet radiation has a high bactericidal efficiency and is a simple, economical and safe sterilization method. Fig.31 and Fig.32 It can be seen that the composite film has a protective effect on probiotics under strong ultraviolet radiation. The commercially available PE film of the control group film has a high transmittance and cannot shield the probiotics from ultraviolet radiation, and less than 10% of the probiotics survive. It is worth noting that more than 75% of the probiotics still survived under the coverage of the 4% Gel-MAAs / DS composite film, showing excellent anti-ultraviolet performance.

[0231] Fresh-keeping of Strawberries by Gel-MAAs / DS Composite Film

[0232] The Gel-MAAs / DS composite film was used as packaging material to conduct a real-time study on fruit preservation. In this study, strawberry was selected as a food model because it is a perishable fruit with a short storage time.

[0233] To simulate real life, unwrapped strawberries, commercial PE cling film, and Gel-MAAs / DS composite film-wrapped strawberries were compared in a 4°C refrigerator. Fig.33 and Fig.34 As shown. The initial strawberries were plump and bright red in color. For the uncoated strawberries, slight collapse was shown on the 4th day and mold grew on the 14th day, indicating the deterioration of the strawberries; while the strawberries preserved by the commercial PE plastic wrap showed signs of decay on the twelfth day. After the 16th day, more and more mold spots appeared, and the appearance of strawberry decay and darkening color became more and more obvious; the strawberries covered with the Gel-MAAs / DS composite film did not rot, and the appearance, color and plumpness were good. Even on the 16th day, no white mold was found in the strawberries covered with the Gel-MAAs / DS composite film. Therefore, the prepared Gel-MAAs / DS composite film significantly extended the shelf life of strawberries. The excellent performance of the Gel-MAAs / DS composite film is due to its low WVP, low hydrophilicity and UV resistance. The weight loss rate of all strawberries showed an upward trend within 16 days of storage, which was due to the high moisture content of the strawberries, and the transpiration and respiration increased the water loss rate. The low WVP and low hydrophilicity of the Gel-MAAs / DS composite film reduce the respiration and oxidation of strawberries to a certain extent by limiting water evaporation. The weight loss rate of strawberries in the blank control group was significantly higher than that in the PE cling film group and the test group. This is mainly because the strawberries in the control group were not covered by the film, so the water in the strawberries was more easily lost to the air. The water vapor permeability of PE cling film is the lowest, but it is precisely because the high water content in the environment is conducive to the growth of mold, which is not conducive to the preservation of strawberries.

[0234] Biocompatibility of Gel-MAAs / DS composite membrane

[0235] The cytotoxicity of Gel-MAAs / DS composite membrane is also one of the important evaluation indicators for it as a bio-based composite membrane. The CCK8 method was used to detect the cytotoxicity of the Gel-MAAs / DS composite membrane extract on L-929 cells. The extract was co-cultured with L-929 cells for 24 hours. Fig.35 As shown, the cell survival rate of these groups of composite membranes exceeded 100%, indicating that Sal and HA as part of the material itself can promote the proliferation of L929 cells. This is because these two polysaccharides provide nutrients for cell proliferation and differentiation, and the cell survival rate is still higher than 90%. The experimental results show that the Gel-MAAs / DS composite membrane has good biocompatibility.

[0236] from Fig.36The results of live / dead cell staining were consistent with those of CCK8. After 24 hours of incubation of L929 cells with Gel-MAAs / DS composite membrane extract, most L929 cells maintained spindle-shaped morphology and were evenly distributed and green living cells, with basically no red blood cells and dead cells, indicating that the Gel-MAAs / DS composite membrane extract had no cytotoxicity and had good biocompatibility.

[0237] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for extracting mycosporin-like amino acids from Porphyra yezoensis, characterized in that: The steps include: After crushing Porphyra yezoensis, adding cellulase thereto, and then adding ethanol solution with a mass concentration of 20-30%, extracting at 40-50° C. for 1-3 hours, ultrasonically extracting for 20-40 minutes, centrifuging and separating, and collecting the supernatant; Add 2-6 times the volume of 90-97% ethanol to the supernatant, freeze the alcohol precipitation, freeze centrifuge, freeze-dry the supernatant, and the freeze-dried product is the mycosporin-like amino acid.

2. The method for extracting mycosporin-like amino acids from Porphyra yezoensis according to claim 1, characterized in that: The mass ratio of Porphyra yezoensis to cellulase is 1000:1-2.

3. The method for extracting mycosporin-like amino acids from Porphyra yezoensis according to claim 1, characterized in that: The method also includes the step of purifying the prepared crude mycosporin-like amino acid product, and the purification method is: loading the crude mycosporin-like amino acid product solution onto a Qapto Q column, using ultrapure water to balance the ion exchange column at a flow rate of 0.5-1.5 mL / min; then using 0.5-1.5 mol / L NaCl elution buffer to perform linear elution at a flow rate of 0.5-1.5 mL / min, and collecting the elution peak solution with an absorbance of 334 nm at ultraviolet absorption.

4. A method for preparing a gelatin-mycosporine-like amino acid-dialdehyde starch composite film, characterized in that: The steps include: Add a cross-linking agent to the gelatin solution, activate it for a set time, add N-hydroxysuccinimide, and then add mycosporin-like amino acids, couple it for a set time under weak acid conditions and in the dark, to obtain Gel-MAAs; Dissolve Gel-MAAs in water to obtain a complex solution; Dissolving dialdehyde starch in water, gelatinizing, and adjusting to weak alkalinity to obtain a dialdehyde starch solution; Add the dialdehyde starch solution dropwise to the complex solution, mix well, react at 35-45°C for 1-3h, add 1-5%, w / v glycerol, degas by ultrasonication, pour the membrane solution into a mold, and dry to obtain the membrane.

5. The method for preparing the gelatin-mycosporine-like amino acid-dialdehyde starch composite film according to claim 4, characterized in that: The mass ratio of Gel-MAAs complex to dialdehyde starch is 2-5:3; Preferably, in the membrane solution, the content of glycerol is 3%, the content of Gel-MAAs is 4%, and the content of dialdehyde starch is 3%, where % is w / v.

6. The method for preparing the gelatin-mycosporine-like amino acid-dialdehyde starch composite film according to claim 4, characterized in that: The pH value of the dialdehyde starch solution is 9-11, preferably 10.

7. The method for preparing the gelatin-mycosporine-like amino acid-dialdehyde starch composite film according to claim 4, characterized in that: The cross-linking agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide; Preferably, the mass ratio of gelatin, EDC, N-hydroxysuccinimide and mycosporin-like amino acid is 0.8-1.2:0.2-0.3:0.1-0.2:0.8-1.

2.

8. The method for preparing the gelatin-mycosporine-like amino acid-dialdehyde starch composite film according to claim 4, characterized in that: Activation time is 20-40min; Preferably, the weakly acidic pH value is 4-6, preferably 5.

9. A gelatin-mycosporine-like amino acid-dialdehyde starch composite film, characterized in that: Prepared by the preparation method described in any one of claims 4 to 8.

10. Use of the gelatin-mycosporine-like amino acid-dialdehyde starch composite film according to claim 9 in the preparation of UV-resistant devices.

Citation Information

Patent Citations

  • Method for extracting mycosporine-like amino acids from euphausua superba

    CN105037201A

  • Method of functionalization of a biopolymer and method of cross-linking thereof

    WO2024196271A2